Pengaruh Karakteristik Perusahaan Terhadap Tingkat Kelengkapan Sukarela - Linda Yuliani Hutadjulu; Ulfah Rizky Muslimin (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This research aims to obtain empirical evidence about effect of firm characteristics and profitability on the level of completeness of voluntary disclosure. Company characteristics consisting of company size, profitability, age of record and composition of the independent board of commissioners. Independent variables of this research are, firm size, profitability, age of record, and the composition of the independent board of commissioners, and the dependent variable is voluntary disclosure.This research use a quantitative approach with the research samples are financial sector companies and the consumer goods industry sector that listed on Indonesia Stock Exchange for the period 2020. Data analysis technique that used is multiple linear regression.The results of this research indicate that company size (Size), profitability, listing Age and proportion of the board of commissioners have no effect on the level of completeness the voluntary disclosure.